2009 IEEE International Conference on Intelligent Computing and Intelligent Systems 2009
DOI: 10.1109/icicisys.2009.5358243
|View full text |Cite
|
Sign up to set email alerts
|

The compensation capacitors fault detection method of jointless track circuit based on DBWT and WR

Abstract: This paper uses transport-line theory to construct equivalent model of jointless track circuit under shunted state and analyses the principle of track induced circuit in the disconnection fault of compensation capacitor based on the model. At the same time, according to the work principle of cab signal and the consistent changes relationship between cab signal induced voltage and short-circuit current of the track circuit, the induced voltage recorded by cab signal is denoised by DBWT (discrete binary wavelet … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 3 publications
0
8
0
Order By: Relevance
“…It affects the short-circuit current at the sampling point between the faulty capacitor and the receiver [21], and the deviation in CFSST is influenced accordingly. A deviation in CFSST in one track section is out of the permissive range, and the on-site measurement has shown that there is one faulty compensation capacitor in the track circuit.…”
Section: Discussionmentioning
confidence: 99%
“…It affects the short-circuit current at the sampling point between the faulty capacitor and the receiver [21], and the deviation in CFSST is influenced accordingly. A deviation in CFSST in one track section is out of the permissive range, and the on-site measurement has shown that there is one faulty compensation capacitor in the track circuit.…”
Section: Discussionmentioning
confidence: 99%
“…Zhao et al [10] designed a kind of onboard autotest system to detect the faults of track circuit's compensating capacitors in real time. Zhao et al [11] used the induced voltage recorded by cab signal as fault feature and gave a fault diagnosis method for track circuit based on discrete binary wavelet transform (DBWT) and wavelet ridge (WR), finally detecting the changes of instantaneous frequency to diagnose the disconnection fault of compensating capacitor. Zhao et al [12] used the transmission line theory to construct a track circuit model with cascade form of multiple four terminal networks.…”
Section: Introductionmentioning
confidence: 99%
“…Zhao and Mu [14] analyzed induced voltage envelope of cab signal (IVECS) of track circuit by simulation model under different faulty conditions and proposed a compensating capacitor diagnosis method based on adaptive optimal kernel time-frequency representation (AOK-TFR). Zhao et al [15] adopted B-spline DBWT and improved Hilbert-Huang transformation for noise reduction and fault feature retrieve and proposed a diagnosis method for compensating capacitor based on cab signal recorder information. Zhao et al [16] proposed a diagnosis method for compensating capacitor based on the regression model of the shunt current.…”
Section: Introductionmentioning
confidence: 99%
“…In order to reduce maintenance costs and provide a high level of reliability and safety, a great deal of research effort has been directed towards fault detection and diagnosis for trimming capacitors in recent years. One important direction is through analysing the so called short-circuit current signal, and excellent progress has been made using the Dempster-Shafer theory (Oukhellou et al [3]), discrete binary wavelet transform (Zhao et al [4]), partial least squares regression and neural network (Debiolles et al [5]). But most of these methods are only able to detect the first one defective trimming capacitor.…”
Section: Introductionmentioning
confidence: 99%